Maṣlaḥah-Based Appraisal of Consignment Contracts: Micro, Small, and Medium Enterprises (MSME) in Pekanbaru - Pitriyani, Ulan (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: Consignment practices in the micro, small, and medium enterprises (MSMEs) sector are still predominantly based on oral agreements grounded in mutual trust. While simple and flexible, such practices pose significant problems and vulnerabilities, including weak legal certainty, limited documentary evidence in the event of disputes, and an unequal distribution of risks, particularly for consignors. This article examines the legal appraisal of consignment contracts among MSMEs in Pekanbaru through the lens of maṣlaḥah mursalah. The study focuses on the prevalence of oral agreements in practice and the critical need for written contracts to enhance legal certainty and protect the interests of all parties in line with Islamic economic principles. Employing a normative-empirical approach, the research integrates the analysis of statutory provisions and Islamic contract principles with qualitative data gathered from twelve in-depth interviews and a focus group discussion (FGD) involving eight participants. The findings reveal that most consignment arrangements among Pekanbaru MSMEs are trust-based and orally agreed upon, which often leads to disputes and ambiguous delineation of rights and obligations. The maṣlaḥah-based assessment underscores that transitioning to written contracts not only strengthens creditor–debtor relationships but also aligns with the objectives of maqāṣid al-sharīʿah, particularly the protection of wealth (ḥifẓ al-māl). This study provides a contextual mapping of contractual practices among MSMEs, a subject rarely documented empirically in Indonesia, and bridges the theoretical framework of maṣlaḥah with microeconomic realities. The study recommends the development of standardized contract templates and the implementation of Islamic economic literacy programs for MSME actors. Abstrak: Praktik konsinyasi pada sektor UMKM masih didominasi oleh perjanjian lisan yang didasarkan pada rasa saling percaya. Meskipun sederhana dan fleksibel, praktik ini menimbulkan problem dan kerentanan serius, seperti lemahnya kepastian hukum, terbatasnya bukti tertulis ketika sengketa terjadi, serta distribusi risiko yang tidak seimbang, terutama bagi pihak konsinyor. Artikel ini mengkaji penilaian hukum atas praktik kontrak konsinyasi pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Pekanbaru melalui perspektif maṣlaḥah mursalah. Fokus kajian diarahkan pada dominasi perjanjian lisan dalam praktik dan pentingnya perjanjian tertulis untuk memperkuat kepastian hukum serta melindungi para pihak sesuai prinsip ekonomi syariah. Penelitian ini menggunakan pendekatan normatif-empiris. Data dikumpulkan melalui wawancara mendalam terhadap dua belas pelaku UMKM dan Diskusi Kelompok Terarah (FGD) yang melibatkan delapan peserta, serta didukung dengan telaah ketentuan perundang-undangan mengenai konsinyasi dan akad ekonomi syariah. Hasil penelitian menunjukkan sebagian besar praktik konsinyasi UMKM di Pekanbaru berbasis kepercayaan dan perjanjian lisan, sehingga berpotensi menimbulkan sengketa dan ketidakjelasan hak dan kewajiban. Penilaian berbasis maṣlaḥah mursalah menegaskan bahwa peralihan menuju kontrak tertulis tidak hanya memperkuat hubungan kreditur–debitur, tetapi juga sejalan dengan maqāṣid asy-syarīʿah, khususnya dalam perlindungan harta (ḥifẓ al-māl). Studi ini memberikan pemetaan kontekstual praktik kontraktual UMKM yang jarang didokumentasikan secara empiris di Indonesia, sekaligus menjembatani teori maṣlaḥah dengan realitas mikroekonomi. Rekomendasi penelitian mencakup penyusunan template baku untuk kontrak konsinyasi serta program literasi ekonomi syariah bagi pelaku UMKM.